POST-WAR INFRASTRUCTURE RECONSTRUCTION: INNOVATIVE APPROACHES AND INTERNATIONAL EXPERIENCE FOR UKRAINE - Palamar, Mykola (Sworld-Us Conference proceedings, 2025)
The article is devoted to the analysis of modern approaches to post-war infrastructure restoration, taking into account international experience and the possibilities of its adaptation in Ukraine. Innovative solutions in the field of construction, energy,